Modified poly-alpha-olefin, preparation method and application
Modified polyα-olefins are prepared by adding modified carboxylated cellulose nanofibers and polytetrafluoroethylene nanoparticles to polyα-olefins and used to impregnate porous polyimide materials, and the lubricating oil loss and friction wear are solved. The problem of this paper significantly improves its oil retention and friction performance under high-speed conditions, extends service life and reduces wear.
Patent Information
- Application Number
- CN202411542943.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-27
AI Technical Summary
Porous polyimide bearings are worn and damaged due to lubricating oil loss and friction wear under high-speed operation, which affects its long life and stable operation in the aerospace field.
Modified polyα-olefins are prepared by adding modified carboxylated cellulose nanofiber particles and polytetrafluoroethylene nanoparticles to polyα-olefins and used to impregnate porous polyimide materials to enhance their oil retention Capacity and reduce friction wear.
Under high-speed operation conditions, the oil retention rate of porous polyimide materials is improved, the friction coefficient and wear amount is reduced, the service life is extended, and the interface friction is suppressed.
Smart Images

Figure CN119192701A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic polymer compounds and chemical technology, and in particular to a modified poly-alpha-olefin, a preparation method and application thereof. Background Art
[0002] Porous polyimide has excellent thermal stability and mechanical properties, and due to its unique porous structure, it can store lubricants internally to achieve self-lubrication, so it is widely used in aerospace and other fields. As an important component of aerospace bearings, porous polyimide cages can promote the movement of rolling elements and store and distribute lubricants internally during bearing operation, thereby significantly improving the operating stability of the bearing. However, in practical applications, the continuous wear between the porous polyimide cage and the rolling elements will affect the overall stability of the bearing system, resulting in the formation of black products on the surface. On the other hand, the continuous loss of lubricating oil in the porous polyimide material due to centrifugal force and thermal expansion effects will also affect the interface lubrication of the bearing. The combined effect of the two will eventually lead to bearing wear failure and affect its service life.
[0003] Porous polyimide bearings have become one of the bottleneck products that currently restricts the improvement of long-life stable operation of aerospace vehicles. However, there is currently no invention for lubricant modification and optimization in the application scenarios of porous polyimide high-speed bearings. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a modified poly-α-olefin, a preparation method and an application thereof, which can improve the oil retention capacity of a porous polyimide material impregnated with modified lubricating oil under high-speed operation conditions, reduce the friction and wear of the material and extend its service life.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0006] Provided is a method for preparing a modified poly-alpha-olefin, comprising the following steps:
[0007] S1: dispersing carboxylated cellulose nanofibers in anhydrous ethanol to obtain a mixed solution;
[0008] S2: Add silane coupling agent to the mixed solution, and continue stirring and reacting at a constant temperature of 80°C for 4 hours;
[0009] S3: filtering the solution after the reaction is completed to obtain modified carboxylated cellulose nanofibers, washing with anhydrous ethanol and drying to obtain modified carboxylated cellulose nanofiber particles;
[0010] S4: adding modified carboxylated cellulose nanofiber particles and polytetrafluoroethylene nanoparticles to the poly-α-olefin, and uniformly dispersing the particles by high-speed stirring;
[0011] S5: Continue to add emulsifier to the poly-α-olefin, and continue stirring at a constant temperature of 60° C. for 6 hours to make the particles evenly and effectively dispersed in the poly-α-olefin to obtain modified poly-α-olefin.
[0012] Furthermore, the silane coupling agent is KH-560 silane coupling agent; the mass ratio of the carboxylated cellulose nanofibers, the silane coupling agent and anhydrous ethanol is 3-4:6-8:100.
[0013] Furthermore, before adding the silane coupling agent to the mixed solution, 95% pure acetic acid is added to adjust the pH value of the mixed solution to 4, and the mixed solution is continuously stirred while adding the 95% pure acetic acid.
[0014] Furthermore, the mass ratio of the modified carboxylated cellulose nanofiber particles, the polytetrafluoroethylene nanoparticles and the poly-α-olefin is 1.5-2.5:9.5-10.5:100.
[0015] Furthermore, the emulsifier is SP-80 emulsifier, and the mass ratio of the modified carboxylated cellulose nanofiber particles to the emulsifier is 1-2:4-6.
[0016] Furthermore, the length of the carboxylated cellulose nanofibers is 1 to 3 μm, and the cross-sectional diameter is 4 to 10 nm.
[0017] The present invention also provides modified poly-alpha-olefin prepared by the above-mentioned preparation method.
[0018] The present invention also provides an application of the modified poly-α-olefin in aerospace, which is used to improve the oil retention rate of porous polyimide material workpieces, reduce the wear of porous polyimide material workpieces, and improve the blackening of the interface of porous polyimide material workpieces; the specific method is: completely immerse the porous polyimide material workpiece in the modified poly-α-olefin for 24 hours and then take it out to dry.
[0019] Furthermore, when the porous polyimide material workpiece is immersed, it is placed in an environment with a vacuum degree of less than 133Pa.
[0020] The beneficial effects of the present invention are:
[0021] The invention effectively improves the oil retention rate of polyalphaolefin in porous polyimide material by adding modified carboxylated cellulose nanofiber particles and polytetrafluoroethylene nanoparticles to polyalphaolefin for modification, especially under high-speed operation conditions, and the modified lubricating oil can effectively reduce the friction and wear of porous polyimide and its grinding pair materials, and improve the friction and lubrication performance of oil-containing porous polyimide. Under high-speed operation (≥6000rpm), the oil retention rate is increased by 105-125%, the interface friction coefficient is reduced by 10%-25%, the material wear is reduced by 55%-68%, the wear of the grinding pair steel ball is reduced by 52%-70%, and the blackening phenomenon of porous polyimide interface friction is effectively suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a property structure diagram of thermoplastic polyimide sheet;
[0023] Figure 2 It is a comparison diagram of the oil loss rate of porous polyimide samples of poly-α-olefin before and after impregnation modification under different rotation speed conditions;
[0024] Figure 3 This is a comparison of the surface wear of porous polyimide samples before and after impregnation with poly-α-olefin under a 5N friction test load;
[0025] Figure 4 This is a comparison of the surface wear of porous polyimide samples before and after impregnation with poly-α-olefin under a 10N friction test load;
[0026] Figure 5 This is a comparison of the surface wear of porous polyimide samples before and after impregnation with poly-α-olefin under a friction test load of 15N;
[0027] Figure 6 This is a comparison chart of friction coefficient and wear volume after different friction test loads of porous polyimide samples before and after impregnation modification with poly-α-olefin. DETAILED DESCRIPTION
[0028] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0029] Example 1
[0030] The preparation of modified poly-alpha-olefin comprises the following steps:
[0031] S1: Put 3 parts of carboxylated cellulose nanofibers into 100 ml of anhydrous ethanol, stir at high speed for 20 minutes until the mixture is evenly dispersed; the length of the carboxylated cellulose nanofibers is 1-3 μm, and the cross-sectional diameter is 4-10 nm; adjust the pH value of the mixture to 4 using 95% pure acetic acid, and continue to stir the mixture while adding 95% pure acetic acid. In specific implementation, 4 parts of carboxylated cellulose nanofibers can also be added to every 100 ml of anhydrous ethanol;
[0032] S2: Add 7 parts of KH-560 silane coupling agent to the mixed solution after adjusting the pH value, and continue stirring and reacting at a constant temperature of 80° C. for 4 hours; in specific implementation, the mass parts of KH-560 silane coupling agent can also be 6 parts or 8 parts;
[0033] S3: filtering the solution after the reaction is completed to obtain modified carboxylated cellulose nanofibers, washing with anhydrous ethanol and drying to obtain modified carboxylated cellulose nanofiber particles (M-CNFC);
[0034] S4: adding 2 g of M-CNFC and 10 g of polytetrafluoroethylene nanoparticles to 100 g of poly-α-olefin, and stirring at high speed for 30 min to evenly disperse the particles; in specific implementation, the amount of M-CNFC added to each 100 g of poly-α-olefin can also be 1.5 g or 2.5 g, and the amount of polytetrafluoroethylene nanoparticles added to each 100 g of poly-α-olefin can also be 9.5 g or 10.5 g;
[0035] S5: Continue to add 5g of SP-80 emulsifier to the poly-α-olefin, and continue stirring at a constant temperature of 60°C for 6h to make the particles evenly and effectively dispersed in the poly-α-olefin to obtain modified poly-α-olefin. In specific implementation, the amount of SP-80 emulsifier added to every 100g of poly-α-olefin can also be 4g or 6g;
[0036] Example 2
[0037] Take a thermoplastic polyimide sheet (PPI) with a size of 15mm×15mm×5mm as the test sample; the properties and structure of the thermoplastic polyimide sheet are as follows Figure 1 As shown, Figure 1 a is the molecular structure of thermoplastic polyimide. The pore structure of PPI was tested using an automatic mercury porosimeter (AutoPore IV 9500, Microcrystalline Instruments, USA). The test results are shown in Figure 1 b and Figure 1 As shown in c, Figure 1 b and Figure 1c shows that the average pore size of the thermoplastic polyimide sheet is about 2.21 μm, and the porosity is about 16.67%. The surface roughness of the thermoplastic polyimide sheet is about 1.3 μm as measured by the white light interferometer Super View W1, and the surface roughness of the thermoplastic polyimide sheet is about 1.3 μm as measured by the scanning electron microscope Zeiss Gemini 300. Figure 1 The cross-sectional electron micrograph shown in d and Figure 1 Surface electron microscopy image shown in e.
[0038] Take two identical test samples and impregnate them with polyα-olefin (original oil) and modified polyα-olefin (modified oil) prepared in Example 1 respectively. The impregnation process is as follows: under a vacuum degree of <133Pa, completely immerse the test sample in polyα-olefin or modified polyα-olefin for 24h to obtain a PPI sample impregnated with original oil and a PPI sample impregnated with modified oil.
[0039] The PPI samples soaked in original oil and the PPI samples soaked in modified oil were placed in a high-speed centrifuge model TG-16WS for a high-speed oil-spinning experiment for 1 hour to test their oil loss rates under different speed conditions. The oil loss rate calculation formula is as follows:
[0040]
[0041] Among them, m 0 is the mass of the test sample before oil immersion, m 1 is the mass of the test sample after oil immersion, m t is the mass of the test sample after centrifugation for t minutes.
[0042] The oil loss rate under different speed conditions is as follows Figure 2 As shown by Figure 2 It can be seen that the PPI sample immersed in modified oil can effectively reduce the loss of lubricating oil due to centrifugal action under the condition of 1000-8000RPM speed, especially under the condition of higher speed greater than or equal to 6000RPM. From this, the oil retention rate of oil-containing porous polyimide under different speed conditions can be further calculated. The oil retention rate represents the oil retention capacity of the oil-containing porous polyimide material after oil immersion, which directly affects the service life of the porous polyimide under long-term operation conditions. The oil retention rate calculation formula is as follows:
[0043]
[0044] It is calculated that at a speed of 8000 RPM, the oil retention rate of the PPI sample immersed in modified oil is increased by 120.6% compared with the oil retention rate of the PPI sample immersed in original oil.
[0045] Furthermore, a high-speed friction and wear testing machine of UMT-TriboLab, Bruker was used, and a typical bearing steel ball (GCr15) with a diameter of 6.35 mm was used as the grinding pair steel ball. The PPI samples immersed in the original oil and the PPI samples immersed in the modified oil were tested respectively. The friction and wear performance under three load conditions of 5N, 10N and 15N was selected as the test mode. The speed was 100mm / s and the time was 1h. After the test, the samples and the grinding pair steel balls were detected using a metallographic microscope of Axio Lab.A1, Zeiss, and the morphology and cross-section of the samples were scanned and photographed using a white light interferometer of Super View W1. The results are shown in the figure. Figure 3-6 shown.
[0046] Among them, the test results under 5N load conditions are as follows Figure 3 As shown, Figure 3 a is the optical microscope image of the wear scar position of the PPI sample immersed in the original oil. Figure 3 b is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in the original oil. Figure 3 c is the optical microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in the original oil;
[0047] Figure 3 d is the optical microscopy image of the wear scar position of the PPI sample immersed in modified oil. Figure 3 e is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in modified oil. Figure 3 f is a light microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in modified oil;
[0048] The test results under 10N load conditions are as follows Figure 4 As shown, Figure 4 a is the optical microscope image of the wear scar position of the PPI sample immersed in the original oil. Figure 4 b is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in the original oil. Figure 4 c is the optical microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in the original oil;
[0049] Figure 4 d is the optical microscopy image of the wear scar position of the PPI sample immersed in modified oil. Figure 4 e is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in modified oil. Figure 4 f is a light microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in modified oil;
[0050] The test results under 15N load condition are as follows Figure 5 As shown, Figure 5 a is the optical microscope image of the wear scar position of the PPI sample immersed in the original oil. Figure 5 b is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in the original oil. Figure 5 c is the optical microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in the original oil;
[0051] Figure 5 d is the optical microscopy image of the wear scar position of the PPI sample immersed in modified oil. Figure 5 e is the morphology and cross-sectional view of the wear scar position of the PPI sample immersed in modified oil. Figure 5 f is a light microscopic image of the wear spot position of the steel ball of the grinding pair of the PPI sample immersed in modified oil;
[0052] in, Figure 6 (a) is a comparison chart of the friction coefficient of the PPI sample immersed in PAO oil and the PPI sample immersed in modified PAO oil under the test condition of 5N. Figure 6 (b) is a comparison chart of the friction coefficient of the PPI sample immersed in PAO oil and the PPI sample immersed in modified PAO oil under the test condition of 10N. Figure 6 (c) is a comparison chart of the friction coefficient of the PPI sample soaked in PAO oil and the PPI sample soaked in modified PAO oil under the test condition of 15N. Figure 6 (d) is a comparison of the wear volumes of the PPI samples soaked in PAO oil and the PPI samples soaked in modified PAO oil after friction tests under different load conditions. Figure 6 (e) is a comparison chart of the wear volume of the corresponding grinding pair steel balls after the PPI sample immersed in PAO oil and the PPI sample immersed in modified PAO oil were subjected to friction tests under different load conditions.
[0053] Depend on Figure 3-Figure 6 It can be seen that the porous polyimide samples impregnated with modified PAO oil show better friction performance under the test conditions of 5-15N. Under the same test conditions, the wear volume of porous polyimide and the grinding pair steel ball is significantly reduced. The wear volume is estimated by the wear volume. Specifically, under the 5N condition, the wear volume of porous polyimide is reduced by 64.7%, and the wear volume of the grinding pair steel ball is reduced by 66.2%. Under the 10N condition, the wear volume of porous polyimide is reduced by 65.3%, and the wear volume of the grinding pair steel ball is reduced by 68.3%. Under the 15N condition, the wear volume of porous polyimide is reduced by 56.3%, and the wear volume of the grinding pair steel ball is reduced by 65.1%. The friction coefficient also decreases under different load conditions. Specifically, under the 5N condition, the friction coefficient is reduced by 21.1%, under the 10N condition, the friction coefficient is reduced by 13.6%, and under the 15N condition, the friction coefficient is reduced by 18.7%. In addition, Figure 3-5 From the comparison of the surface optical microscopy images of different samples, it can be seen that the blackening phenomenon in the wear scar area on the surface of the oil-immersed porous polyimide material has been effectively suppressed.
Claims
1. A method for preparing a modified poly-α-olefin, characterized in that: The steps include: S1: dispersing carboxylated cellulose nanofibers in anhydrous ethanol to obtain a mixed solution; S2: Add silane coupling agent to the mixed solution, and continue stirring and reacting at a constant temperature of 80°C for 4 hours; S3: filtering the solution after the reaction is completed to obtain modified carboxylated cellulose nanofibers, washing with anhydrous ethanol and drying to obtain modified carboxylated cellulose nanofiber particles; S4: adding modified carboxylated cellulose nanofiber particles and polytetrafluoroethylene nanoparticles to the poly-α-olefin, and uniformly dispersing the particles by high-speed stirring; S5: Continue to add emulsifier to the poly-α-olefin, and continue stirring at a constant temperature of 60° C. for 6 hours to make the particles evenly and effectively dispersed in the poly-α-olefin to obtain modified poly-α-olefin.
2. The method for preparing modified poly-α-olefin according to claim 1, characterized in that: The silane coupling agent is KH-560 silane coupling agent; the mass ratio of the carboxylated cellulose nanofibers, the silane coupling agent and anhydrous ethanol is 3-4:6-8:
100.
3. The method for preparing modified poly-α-olefin according to claim 1, characterized in that: Before adding the silane coupling agent to the mixed solution, 95% pure acetic acid was added to adjust the pH value of the mixed solution to 4, and the mixed solution was continuously stirred while adding the 95% pure acetic acid.
4. The method for preparing modified poly-α-olefin according to claim 1, characterized in that: The mass ratio of the modified carboxylated cellulose nanofiber particles, the polytetrafluoroethylene nanoparticles and the poly-α-olefin is 1.5-2.5:9.5-10.5:
100.
5. The method for preparing modified poly-α-olefin according to claim 1, characterized in that: The emulsifier is SP-80 emulsifier, and the mass ratio of the modified carboxylated cellulose nanofiber particles to the emulsifier is 1-2:4-6.
6. The method for preparing modified poly-α-olefin according to claim 1, characterized in that: The length of the carboxylated cellulose nanofiber is 1-3 μm, and the cross-sectional diameter is 4-10 nm.
7. The modified poly-α-olefin prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the modified poly-α-olefin according to claim 7 in aerospace, characterized in that: Used to improve the oil retention rate of porous polyimide material workpieces, reduce the wear of porous polyimide material workpieces and improve the wear and blackening of the interface of porous polyimide material workpieces; the specific method is: completely immerse the porous polyimide material workpiece in modified polyalphaolefin for 24 hours and then take it out and dry it.
9. The use of the modified poly-α-olefin according to claim 8 in aerospace, characterized in that: When the porous polyimide material workpiece is immersed, it is placed in an environment with a vacuum degree of less than 133Pa.